2011
DOI: 10.1371/journal.pone.0016202
|View full text |Cite
|
Sign up to set email alerts
|

It Takes Two–Skilled Recognition of Objects Engages Lateral Areas in Both Hemispheres

Abstract: Our object recognition abilities, a direct product of our experience with objects, are fine-tuned to perfection. Left temporal and lateral areas along the dorsal, action related stream, as well as left infero-temporal areas along the ventral, object related stream are engaged in object recognition. Here we show that expertise modulates the activity of dorsal areas in the recognition of man-made objects with clearly specified functions. Expert chess players were faster than chess novices in identifying chess ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
66
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 71 publications
10
66
0
2
Order By: Relevance
“…Specifically, regions engaged by Scrabble experts in the SDT were more widespread, including extensive activity in posterior visual regions, as well as temporal and parietal language regions and their right hemisphere homologs. These results align with the expertise literature, with respect to recruitment of additional regions as well as greater bilateral activity in expert groups (Bilalić et al, 2011, 2012; Guida et al, 2012; Proverbio et al, 2013). In contrast, the control group engaged fewer regions, with activity found predominantly in temporal and frontal regions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, regions engaged by Scrabble experts in the SDT were more widespread, including extensive activity in posterior visual regions, as well as temporal and parietal language regions and their right hemisphere homologs. These results align with the expertise literature, with respect to recruitment of additional regions as well as greater bilateral activity in expert groups (Bilalić et al, 2011, 2012; Guida et al, 2012; Proverbio et al, 2013). In contrast, the control group engaged fewer regions, with activity found predominantly in temporal and frontal regions.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that reduced activity compared to controls may be associated with increased task efficiency in the Scrabble experts, in line with the intelligence literature (e.g., Haier et al, 1992; Jausovec and Jausovec, 2004). However, previous studies in the expertise literature suggest that functional reorganization and greater bilateral activity underlies expert performance (e.g., Bilalić et al, 2011, 2012; Guida et al, 2012; Proverbio et al, 2013). Thus, evidence for far transfer in the current study may include greater activity in bilateral visual-perceptual and long-term working memory regions for Scrabble experts compared to controls during the SDT.…”
Section: Introductionmentioning
confidence: 95%
“…Research in chess experts provided a large body of data addressing neuronal correlates of visual skills (Bilalić et al, 2010, 2011a,b, 2012; Krawczyk et al, 2011). For research on object recognition and visual integration chess appears to be particularly suitable as it features various, clearly distinguishable individual objects that allow the composition of complex stimulus configurations with graded complexity.…”
Section: Introductionmentioning
confidence: 99%
“…A typical chess position featuring numerous individual objects represents a single meaningful unit to chess experts. In a recent series of fMRI studies, Bilalić et al (2010, 2011a,b, 2012) demonstrated that chess experts also showed different neuronal response patterns in the ventral visual system compared to novices. Typically, chess experts showed higher signal increases mostly in the temporal lobe compared to novices during the observation of chess stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation